BEYOND INCLUSION: UNCOVERING THE ROLE OF INCLUSIVE LEARNING IN SHAPING STUDENTS' PERSPECTIVE-TAKING - Nurul Fajriyah; Abu Hasan Agus R; Izzatul Munawwaroh; Syahzadi Hina Sain (Nurul Jadid University, 2026)
This study aims to uncover the role of inclusive learning in shaping students' perspective-taking abilities through social interactions and pedagogical practices in the classroom. The study employed a qualitative approach with a case study to gain a deeper understanding of the contextual learning process. Data were collected through observation, in-depth interviews, and documentation, then analyzed interactively through systematic data reduction, data presentation, and conclusion drawing. The results indicate that students' perspective-taking abilities are formed through two main interrelated mechanisms. First, structured social interactions, such as heterogeneous group discussions, collaborative work, and reflective dialogue, encourage students to understand, compare, and reflect on others' perspectives more deeply. Second, teachers' pedagogical practices, such as the use of reflective questions, facilitating open discussions, participatory approaches, and empathy modeling, act as guides and strengthen these processes. These findings confirm that inclusive learning functions not only as a space for social integration but also as a transformational process that sustainably shapes students' socio-cognitive abilities. This study makes both theoretical and practical contributions by emphasizing the importance of quality interactions and pedagogical strategies in developing the ability to understand others' perspectives in a more reflective, adaptive, and contextual manner.